2017
DOI: 10.21608/auej.2017.19285
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Different Control Techniques Applied on 6 Dof Robot Arm

Abstract: Most of the industrial controllers used today for 6 DOF robot arm utilize PID controllers. Using PID controller without tuning method leads to response with unsuitable time-domain specifications (maximum-overshot, settling-time, rise-time, …). Ziegler-Nichols method was introduced as the conventional method for tuning the PID controller. By using this method, the enhancement of the response time-domain specifications is not sufficient. Recently, fuzzy logic with and without PID-controller, and genetic algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It has been reported that a system with a PID-fuzzy logic tuning method outperforms a conventional PID tuned method. A comparative analysis is conducted to determine the optimal tuning strategy for controlling a 6-DOF robot arm [9]. The study compares three types of control methods with different tuning methods, namely, the Ziegler-Nichols PID controllers, the fuzzy logic controllers, and the Fuzzy-PID controllers.…”
Section: Mamdani Fuzzy Interference System (Fis)mentioning
confidence: 99%
“…It has been reported that a system with a PID-fuzzy logic tuning method outperforms a conventional PID tuned method. A comparative analysis is conducted to determine the optimal tuning strategy for controlling a 6-DOF robot arm [9]. The study compares three types of control methods with different tuning methods, namely, the Ziegler-Nichols PID controllers, the fuzzy logic controllers, and the Fuzzy-PID controllers.…”
Section: Mamdani Fuzzy Interference System (Fis)mentioning
confidence: 99%